FAKTOR-FAKTOR PENYEBAB MOBILITAS ANGKATAN KERJA USIA MUDA DI DESA ADINUSO KABUPATEN BATANG - Susanti, Dewi (Solidarity: Journal of Education, Society and Culture, 2012)
This article examines the factors that led to the mobility of the workforce out of the village youth in the village of Adinuso and its consequences. The results of this study indicate that the mobility of the workforce at a young age Adinuso village is driven by the push factors which consists of the desire for independence, poverty, income rndahnya work in cottage industry of embroidery, the desire to succeed as their peers, looking for experience, and limitations facilities and infrastructure in the village of Adinuso. The mobility is driven by the pull factor which consists of the number of jobs, wages are attractive, and modernization. The impact of young labor force mobility of socio-economic life of the village of Adinuso the increased prosperity, less productive workers in the cottage industry of embroidery fabric, less manpower in the agricultural sector, changes in lifestyle, and reduce social deviation. The dominant driving factors (push factor) of mobility of young labor force is poverty, while the dominant pull factors (pull factors) that affects predominantly young workforce mobility in the Village Adionuso are many factors in urban employment. The mobility of the labor force this young age have negative and positive impact on socio-economic and cultural life of the village community.